Pigs ahoy! - McPhail, David (New York : Puffin Books, 1995)
A child joins an ocean cruise on which some bad mannered pigs create disaster while on board, and when the child returns home, a great surprise awaits him.
Keywords: Cruise ships-Fiction; Pigs-Fiction; Voyages and travels-Fiction; Stories in rhyme